The effect of health anxiety on postoperative analgesia requirement and anesthesia recovery in patients undergoing laparoscopic cholecystectomy - Cigdem Unal Kantekin; Yunus Hacimusalar; Gamze Talih; Ozgul Karaaslan (SERNEV, 2019)
Introduction: Health anxiety is the excessively negative interpretation of normalphysical signs in an individual with no physical disease. Having knowledgeinformation about the health anxiety levels of patients is one of the criteriathat will affect the treatment of the patients' pain. The aim of this study wasto evaluate the preoperative health anxiety of laparoscopic cholecystectomypatients together with the perception of postoperative pain and the requirementfor analgesia.Methods: Thestudy included 41 patients of American Society of Anesthesiologists(ASA) gradeI-II, aged 18-65 years who were to undergo a laparoscopic cholecystectomyoperation and a control group of 40 healthy individuals. The Health AnxietyInventory was applied to the patients preoperatively and to the control group.In the postoperative period, the patients were followed up for 24 hours with apatient-controlled analgesia device prepared with tramadol. Visuel AnalogScale(VAS) values of patients were below 4 due to the use of patient controlledanalgesia device. Total analgesic consumption was recorded. The results were comparedstatistically.Results: No significant difference was determined between the patient and controlgroups in respect of age, gender and body mass index (p gt;0.05). The VAS scoreof all the patients was less than four. The mean total tramadol consumption ofthe patients in the first 24 hours postoperatively was 221.58±73.06. Theanalgesia consumption of female patients was significantly higher than that ofmales (p=0.013). The health anxiety results of the patient group were found tobe significantly higher than the control group (p lt;0.001). A positivecorrelation was determined in the patient group between health anxiety and thetotal analgesia requirement (r=0.813, p lt;0.01).Conclusions: In conclusion, high level of analgesia consumption was determined inthose with high health anxiety and in female patients. When planningpostoperative pain treatment, consideration of the gender of the patient andthe level of health anxiety will make a positive contribution to the treatment.